KUALITAS NATA DE CITRULLUS MENGGUNAKAN BERBAGAI MACAM STARTER - Fifendy, Mades; Annisah, Nur (IAIN Batusangkar, 2012)
Low-calorie watermelon flesh contains as much as 93.4% water, 0.5% protein, 5.3% carbohydrate, fat 0.1%, fiber 0.2%, ash 0.5%, Vitamin A, Vitamin B and vitamin C. Chemical content of watermelon, especially the carbohydrate content can be used as an ingredient to make nata de Citrullus. The nata formation is strongly influenced by the carbohydrate content, pH, nitrogen content in the substrate and stable environmental condition. The purpose of this study was to determine the best starter. This study was carried out from February to June 2011. The research design was a Completely Randomized Design (CRD) with 6 (six) treatments, namely coconut water starter (A), watermelon starter (B), pineapple skin starter (C), banana peels starter (D), bangkuang starter (E) and tomato starter (F). The parameters tested were the thickness of nata, wet weight and dry weight, firmness and organoleptic tests. Data were analyzed by using ANOVA and further test HSD at the level of 5% and 1%. The result of this study indicates that the use of a wide range of real starter do not affect the thickness. However there were significant difference at the level of 5% of the wet weight, and it was significantly different at the level of 1% of the dry weight. Finally, it does not affect significantly on organoleptic test (flavor, color, taste and texture).